RASIO BINTIL AKAR DAN HASIL TANAMAN KEDELAI (Glycine Max (L) Merr.) DENGAN PERBEDAAN DOSIS APLIKASI PUPUK HAYATI VP3 DAN LAMA INDUKSI LISTRIK - ayu azhariah; Siti Muslikah; Novi Arfarita (AGRONISMA, 2021)
The purpose of this study was to determine the effect of VP3 biofertilizer application and the duration of electrical induction on the growth, yield, and ratio of soybean root nodules. This research has conducted at the Griya Santa Experimental Ground, Brawijaya University, Malang, and the Microbiology Laboratory of the Islamic University of Malang from October 2020 to January 2021. The research design used was a Randomized Block Design (RAK) which consisted of 13 treatments and was repeated three times. The results showed that increasing the dose of VP3 biofertilizer and the duration of electrical induction was able to increase the total number of root nodules in the V1L3 treatment (100% VP3 biofertilizer + 90 minutes electric hypernym). Meanwhile, the yield of soybean plants treated with V2L1 (Biological fertilizer VP3 200% + 30 minutes electrical induction) and V1L2 (Biological fertilizer VP3 200% + electric hypernym 60 minutes) showed significant results.